Coins, bodies, games, and gold : the politics of meaning in archaic Greece - Kurke, Leslie (Princeton, NJ : Princeton University Press, 1999)
The invention of coinage in ancient Greece provided an arena in which rival political groups struggled to imprint their views on the world. This book analyses the ideological functions of Greek coinage.
The language of metals -- Tyrants and transgression: Darius and Amasis -- Counterfeiting and gift exchange: the fate of Polykrates -- Kroisos and the oracular economy -- The Hetaira and the Pornē -- Herodotus's traffic on women -- Games people play -- Minting citizens.
Includes bibliographical references (pages 337-364) and indexes.
Print version record.
JSTOR
Keywords: Greece -- Antiquities; Greece -- Civilization -- To 146 B.C.; Meaning (Psychology) -- Greece; Coins, Greek -- Greece -- History; Greece -- Social conditions -- To 146 B.C.; Meaning (Psychology); Grèce -- Antiquités.; Grèce -- Civilisation -- Jusqu'à 146 av. J.-C.; Signification (Psychologie) -- Grèce.; Monnaies grecques -- Grèce -- Histoire; Grèce -- Conditions sociales -- Jusqu'à 146 av. J.-C.; HISTORY -- Ancient -- Greece; Antiquities; Civilization; Coins, Greek; Meaning (Psychology); Social conditions; Greece; Münzbild; Sozialstatus; Griechenland; Münzwesen; Politik; Sociale status; Munten; Betekenis; Griekse oudheid; Kultur -- Griechenland (altes) -- Geschichte Archaische Zeit; Münzprägung -- Griechenland (altes); Griechenland (altes) -- Geschichte Archaische Zeit; Zivilisation -- Geld -- Griechenland (Altertum); Geld -- Zivilisation -- Griechenland (Altertum); Griechenland (Altertum) -- Geld -- Zivilisation; Meaning (Psychology) -- Greece; Coins, Greek -- Greece; Greece -- Social life and customs; Griechenland; Altertum; Ideologie; Sozialgeschichte; Kulturgeschichte; Geldgeschichte; To 146 B.C.; History